The Impact of Parenting Style Towards Ember’s Character in Elemental Movie - Jasin, Nur Alya (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
Parenting style, defined as the combination of strategies parents use to raise their children, is a crucial factor in shaping a child’s emotional and psychological development. In animated films, parenting styles are often portrayed through character interactions, offering insight into how familial relationships influence identity. this study explores the impact of parenting style on Ember Lumen’s character in Elemental: Forces of Nature (2023), directed by Peter Sohn. Using Baumrind’s parenting theory along with Maccoby and Martin’s framework, the research applies a psychological literary approach to analyze Bernie Lumen’s parenting. The findings reveal that Bernie primarily demonstrates authoritative parenting, characterized by high expectations and emotional support, which contributes to Ember’s growth in responsibility, emotional regulation, and self-awareness. However, occasional authoritarian and permissive tendencies also emerge, creating internal conflict for Ember as she struggles between fulfilling her father’s expectations and pursuing her own dreams. This study highlights how parenting styles in film narratives can reflect real-life dynamics, influencing a character’s identity formation and emotional journey.